Reflective Teaching in the Context of Community - Reese, Ruth Anne (The Asbury journal, 2008)
This essay delves into the feelings of fear and self-doubt that a rookie teacher experienced her first semester as an adjunct professor and how, through reacting and reflection, she was able to regain her confidence and approach the profession with renewed confidence and joy. Drawing wisdom and gleaning practical tools from Brookfield's Becoming a Critically Reflective Teacher and Parker's The Courage to Teach: Exploring the Inner Landscape of a Teacher's Life, the author learned the value of deliberate conversations with colleagues and was reminded that she and her students are joint-learners.